Cytopenia occurrence in kidney transplant recipients within early post-transplant period - Atefeh Jafari; Parisa Najivash; Mohammad-Reza Khatami; Simin Dashti-Khavidaki (Wolters Kluwer Medknow Publications, 2017)
Objective: This study assessed incidence, severity, and time to occurrence of drug-induced leukopenia/thrombocytopenia within 1st month after kidney transplantation. Methods: This cross-sectional study was conducted on newly kidney transplant recipients from two hospitals, Iran. Patients with thrombocytopenia due to acute antibody-mediated rejection were excluded from the study. Demographic, clinical, and laboratory data of patients within the 1st month after transplantation were collected. Findings: Of 213 patients, 14.1% and 66.2% experienced leukopenia and thrombocytopenia, respectively. Cytopenia happened more commonly among patients with thymoglobulin-containing regimen (for leukopenia: 24.6% vs. 0%, P < 0.001; for thrombocytopenia 84.4% vs. 41.8%, P < 0.001). Most leukopenia patients experienced Grades 1 and 2 of leukopenia (46.6% and 40% of patients). Most thrombocytopenic patients showed Grade 1 of thrombocytopenia (78.7%). Cumulative dose of thymoglobulin did not differ between patients with and without leukopenia (5.57 ± 1.13 vs. 5.9 ± 1.96 mg/kg; P = 0.613) or with and without thrombocytopenia (5.87 ± 1.86 vs. 5.56 ± 1.38 mg/kg; P = 0.29). Cytopenia were more common among recipients from deceased compared with from living donors (91.3% vs. 8.7% for leukopenia patients, P = 0.001; 69.9% vs. 33.1% for thrombocytopenia, P = 0.02). More patients with kidney from deceased donors received thymoglobulin in their immunosuppressive regimen (82% vs. 37%; P < 0.001). The median time to leukopenia and thrombocytopenia were 3 days and 1 day, respectively. Conclusion: Among immunosuppressive and prophylactic antimicrobial agents, thymoglobulin is more related to cytopenia; therefore, thymoglobulin dose reduction is recommended as the first intervention to manage cytopenia without need for reduction of its cumulative dose. The higher prevalence of cytopenia among recipients from deceased donors may be related to the higher use of thymoglobulin in these patients.